Traumatic Extensor Tendon Injuries to the Hand: Clinical Anatomy, Biomechanics, and Surgical Procedure Review - Colzani, Giulia; Tos, Pierluigi; Battiston, Bruno; Merolla, Giovanni; Porcellini, Giuseppe; Artiaco, Stefano (Journal of Hand and Microsurgery, 2016)
The extensor apparatus is a complex muscle-tendon system that requires integrity or optimal reconstruction to preserve hand function. Anatomical knowledge and the understanding of physiopathology of extensor tendons are essential for an accurate diagnosis of extensor tendon injuries (ETIs) of the hand and wrist, because these lesions are complex and commonly observed in clinical practice. A careful clinical history and assessment still remain the first step for the diagnosis, followed by US and MR to confirm the suspect of ETI or to investigate some doubtful conditions and rule out associate lesions. During last decades the evolution of surgical techniques and rehabilitative treatment protocol led to gradual improvement in clinical results of ETI treatment and surgical repair. Injury classification into anatomical zones and the evaluation of the characteristics of the lesions are considered key points to select the appropriate treatment for ETI. Both conservative and surgical management can be indicated in ETI, depending on the anatomical zone and on the characteristics of the injuries. As a general rule, an attempt of conservative treatment should be performed when the lesion is expected to have favorable result with nonoperative procedure. Many surgical techniques have been proposed over the time and with favorable results if the tendon injury is not underestimated and adequately treated. Despite recent research findings, a lack of evidence-based knowledge is still observed in surgical treatment and postoperative management of ETI. Further clinical and biomechanical investigations would be advisable to clarify this complex issue.
Keywords: extensor tendon injuries; hand and wrist; surgical treatment; tendon repair; tendon reconstruction